Phenylacetic Acid and Methylphenyl Acetate From the Biocontrol Bacterium Bacillus mycoides BM02 Suppress Spore Germination in Fusarium oxysporum f. sp. lycopersici - Wu, Je-Jia; Huang, Jenn-Wen; Deng, Wen-Ling (Frontiers in Microbiology, 2020)
Bacillus mycoides strain BM02 originally isolated from the tomato rhizosphere was found to have beneficial functions in tomato by promoting plant growth and reducing the severity of Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici (Fol). Cytological experiments demonstrated B. mycoides BM02 reduced Fol invasion by reducing spore attachment and increasing hyphal deformation in hydroponics-grown tomato root tissues. Two volatile antifungal compounds, phenylacetic acid (PAA) and methylphenyl acetate (MPA), were identified from the culture filtrates of B. mycoides BM02 by GC-MS analysis. Chemically synthesized PAA, and to a lower extent MPA, suppressed spore germination but have no effects on the hyphal growth of Fol. Our results indicated that the biocontrol agent B. mycoides BM02 produced an array of bioactive compounds including PAA and MPA to suppress plant diseases caused by Fol and other pathogenic microorganisms.